2016
DOI: 10.1111/jvim.14524
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of Cardiovascular–Renal Disorders in Dogs with Chronic Mitral Valve Disease

Abstract: BackgroundVeterinary literature lacks data about cardiovascular–renal disorders (CvRD) and cardiorenal‐anemia syndrome (CRAS) in dogs.HypothesisA direct correlation exists between ACVIM class and IRIS stage; chronic kidney disease (CKD) complicates chronic mitral valve disease (CMVD) more often than does anemia in dogs.AnimalsOne hundred and fifty‐eight client‐owned dogs with CMVD.MethodsSignalment, physical examination findings, electrocardiography, thoracic radiographs, echocardiography, and blood analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 24 publications
(43 reference statements)
3
44
0
7
Order By: Relevance
“…In humans, renal dysfunction is an important predictor of heart failure outcome 4‐6 . In dogs and cats, azotemia is consistently seen in patients in CHF, 7‐11 with a higher incidence observed in more advanced disease 9‐11 . Although monitoring renal function is considered crucial in management of CHF, 12 the impact of renal function on CHF outcome has not been well documented in cats.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, renal dysfunction is an important predictor of heart failure outcome 4‐6 . In dogs and cats, azotemia is consistently seen in patients in CHF, 7‐11 with a higher incidence observed in more advanced disease 9‐11 . Although monitoring renal function is considered crucial in management of CHF, 12 the impact of renal function on CHF outcome has not been well documented in cats.…”
Section: Introductionmentioning
confidence: 99%
“…The consensus renamed CRS as "Cardiovascular-Renal Disorder" (CRvD) and defined it as a "disease, toxin or druginduced structural and/or functional damage to the kidney and/or cardiovascular system, leading to disruption of the normal interactions between these systems, to the ongoing detriment of one or both" (Pouchelon et al, 2015). Martinelli et al (2016), reported a 25% prevalence of chronic kidney disease (CKD) associated with hyperazotemia in dogs with MMVD. Moreover, the presence of CKD associated to MMVD in dogs decreases survival time (Martinelli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Martinelli et al (2016), reported a 25% prevalence of chronic kidney disease (CKD) associated with hyperazotemia in dogs with MMVD. Moreover, the presence of CKD associated to MMVD in dogs decreases survival time (Martinelli et al, 2016). An early diagnosis of renal impairment in patients affected by cardiovascular disease is therefore very important.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical records were selected according to the following inclusion criteria: complete clinical findings including signalment, history, physical examination, thoracic radiographs, electrocardiogram (ECG) and a diagnosis of DMVD ACVIM class C based on echocardiographic, and Doppler evaluation associated with clinical signs (increased resting respiratory rate, cough, dyspnoea, ascites) [17]. In all subjects the presence and severity of PH were evaluated, based on the TRV.…”
Section: Methodsmentioning
confidence: 99%